Initial pH influences microbial communities composition in dark fermentation of scotta permeate. (3rd May 2018) - Vasmara, Ciro; Pindo, Massimo; Micheletti, Diego; Marchetti, Rosa
Abstract: This study addresses for the first time the influence of initial pH on the evolution of microbial consortia in dark fermentation of scotta permeate, using a high-throughput sequencing approach. Three fermentation phases could be detected: 1) a lag phase with no substantial differences in microbial composition at different initial pH values; 2) an exponential H2 production phase, accompanied by a general increase of Clostridium genus components and higher incidence of Trichococcus genus at neutral and alkaline pH; 3) a final stationary phase, characterized by a general increase of Bifidobacterium and Lactobacillus genera in all reactors. The initial pH value influenced the relative abundance of Trichococcus at 16–48 h of incubation. The metabolic activity of this genus increased the amount of metabolic precursors of H2 so that, when pH lowered to 5.4, clostridia in the reactors with initial alkaline pH become more active H2 -producers than those in the others. Graphical abstract: Highlights: Initial pH influences H2 production from scotta permeate. pH does not affect the microbial alfa diversity between reactors. However, pH does affect the relative abundance of microbial groups. The genus Trichococcus exerts a key role in H2 production at alkaline pH values. Microbial consortia composition can be oriented to optimum H2 production by acting on initial pH.